Islam mystique et révolution armée dans les Balkans ottomans : Vie du Cheikh Bedreddîm Le 'Hallaj des Turcs' (1358/59-1416) - Balivet, Michel (Les Cahiers du Bosphore, 2011)
This book analyzes the life and work of Sheikh Bedreddin of Samavna (1358/9-1416) and his influence on the development of mystical Islam in the Balkans as well as his political importance.